A Study On Prevalence Of Internet Addiction Among Students Of A Private Medical College, Kanchipuram (Journal of Pharmaceutical Negative Results, 2022)
Introduction:Internet has become an essential tool in day to day life1. It has become an important and convenient mode for networking and internet exchange. In 2020, India had nearly 700 million internet users across the country, this figure will grow over 974 million users by 2025. These young people are at risk of developing internet addiction disorder and suffering from health consequences resulting from inadequate sleep as they stay long for chatting, gaming and social status updatesObjectives: To estimate the prevalence of internet addiction and its associated factors among medical undergraduate students.Methodology: This cross sectional study was conducted from January to March 2021 among undergraduate students of a private medical college. A Structured and validated questionnaire i.e. Young’s Internet Addiction Test was used. Data entered in Microsoft Excel, results analyzed using SPSS 25.Results: Among 220 students, 65(29.5%) students were normal, 108(49.1%) were with mild internet addiction, 27 (12.3%) were moderate internet addiction and 20(9.1%) with severe internet addiction. This study concludes there is a significant association between internet addiction with male gender, place of current stay, mode of internet and using internet for academic, social, communication and gaming purposes.Conclusion: There should be proper differentiation between usage and over usage of internet. Awareness must be given to the youth of the nation through proper channel.